315 Is it safe to immediately initiate adjuvant intraperitoneal chemotherapy following bowel resection in patients with newly diagnosed advanced ovarian cancer?. (18th September 2019) - Nica, A; Covens, A; May, T
Abstract : Objectives: To determine if early administration of intraperitoneal chemotherapy (IPC) and intra-operative insertion of an intraperitoneal (IP) port are associated with increased complications in patients who undergo a bowel resection procedure as part of primary cytoreductive surgery. Methods: Retrospective cohort of patients with ovarian cancer at 2 institutions between 2008–2018. Patients included in this study had primary cytoreductive surgery which included one or more small or large bowel resections and either received or were scheduled to receive adjuvant intraperitoneal chemotherapy. Results: The majority of patients had stage III or IV disease (86.2%) and high grade serous histology (91.6%). 120 out of 138 patients (87%) received at least 4 cycles of IPC. A small proportion of patients (5.4%) received all chemotherapy intravenously, despite having had an IP port inserted. Compared to patients who received their first cycle of chemotherapy intravenously (IV), patients who started with IPC were not at increased risk of delayed infection (1.8% vs 1.3% (p=0.8)), IP port related complications which included port obstruction, leakage, infection, pain and erosion (19.6% vs 20% (p=0.96)), or anastomotic leak (3.6% vs 2.7% (p=0.8)). The rates of anastomotic leak (5.6% vs 3.3% (p=0.62)), intra-abdominal infection (16.7% vs 6.7% (p=0.17)) and IP port related complications (24.1% vs 13.3% (p=0.21)) were not statistically different in patients who had intra-operative IP port insertion compared to delayed post-operative insertion. Conclusions: IPC during the first cycle of adjuvant treatment and intra-operative IP port insertion are not associated with increased complications after primary cytoreductive surgery for ovarian cancer which includes a bowel resection.